Greenland, view of Kjerulf Fjord and Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Looking north from inner side of big delta - shown in 28-9. In background, on extreme left, is Riddarborgen (Peak) the N.W. point of Kjerulfs [Kjerulf] Fjord at its junction with Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Mountains and glaciers of Fraenkels Halfo (on the north side of Franz Josef Fjord [Kejser Franz Joseph Fjord]) facing south over Kjerulfs fjord [Kjerulf Fjord] and extreme western part of Suess' Land. In foreground very large icebergs. The one on the right is same as photo 28-7 close up.